Bone mineral density predicts survival in patients with hepatocellular carcinoma and portal vein tumor thrombosis - Lukas Müller; Roman Kloeckner; Lorena Heim; Maximilian Moos; Felix Hahn; Fabian Stoehr; Tilman Emrich; Dirk Graafen; Jan-Peter Grunz; Daniel Pinto dos Santos; Arndt Weinmann; Friedrich Foerster; et al. (PLoS ONE, 2025)
Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related mortality, with portal vein tumor thrombosis (PVTT) being a common complication that significantly worsens prognosis. Recent studies have identified bone mineral density (BMD) as a prognostic factor in patients with HCC; however, its role in patients with PVTT remains unexplored. This retrospective study evaluated the prognostic value of BMD in 462 patients with HCC and PVTT treated between 2005 and 2020. BMD was measured via computed tomography attenuation at the first lumbar vertebra at the time of HCC diagnosis and PVTT onset, using an established threshold of 160 Hounsfield units (HU). Kaplan-Meier analysis assessed overall survival, and multivariate Cox regression adjusted for established prognostic factors. Median BMD was 136 HU (IQR: 113–160) at HCC diagnosis and 134 HU (IQR: 109–159) at PVTT onset. Patients with BMD ≥ 160 HU showed significantly longer overall survival both at HCC diagnosis (10.4 vs. 5.5 months, p < 0.001) and PVTT onset (8.5 vs. 4.7 months, p < 0.001). In multivariate analysis at both time points, BMD remained an independent predictor of survival, alongside tumor growth pattern, therapy, and Albumin-Bilirubin (ALBI) grade (alpha-fetoprotein reached significance only at time of PVTT diagnosis). These findings suggest that BMD independently predicts survival in HCC with PVTT and may enhance prognostic modeling and therapeutic decision-making.